Agile, Effective And Efficient Organization: How Can The Public Sector Achieve This? - Siti Khairiyah Marpaung; Muhammad Irfan Syaebani (Publikasi Indonesia, 2023)
In a dynamic environment, the ability to work with agility, effectiveness, and efficiency is essential to the success of organizations, including public organizations. However, few studies investigate how public organizations in Indonesia apply the strategy to be agile, effective, and efficient. This article can be seen as an attempt to contribute to the Indonesian bureaucracy improvement strategy using qualitative research methods with a phenomenology approach. Based on the research results, it can be concluded that public organizations in Indonesia have implemented strategies to change the culture, structure and work systems supported by the HR management system. All of the strategies need to be carried out simultaneously.